2018
DOI: 10.1002/mbo3.713
|View full text |Cite
|
Sign up to set email alerts
|

RpoN and the Nps and Npa two‐component regulatory system control pilE transcription in commensal Neisseria

Abstract: Over 20 genes are involved in the biogenesis and function of the Neisseria Type IV pilus (Tfp). In the pathogenic species, RpoD and the integration host factor (IHF) protein regulate expression of pilE, encoding the Tfp structural subunit. We previously reported that in commensal species, pilE transcription is regulated by RpoN, IHF, and activator Npa. Npa has many hallmarks of response regulators in two-component regulatory systems, leading us to search for its response regulator partner. We report that Npa p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…In N. musculi, the noncoding DNA segment between the divergently transcribed cps Region A and C contains several potential regulatory sites. The presence of putative Npa and Sigma54 recognition sequences strongly suggests that N. musculi capsule expression is dependent on environmental cues [107,108]. This idea is further supported by the presence of a 17 bp direct repeat upstream of the capsule transport region.…”
Section: Plos Pathogensmentioning
confidence: 80%
“…In N. musculi, the noncoding DNA segment between the divergently transcribed cps Region A and C contains several potential regulatory sites. The presence of putative Npa and Sigma54 recognition sequences strongly suggests that N. musculi capsule expression is dependent on environmental cues [107,108]. This idea is further supported by the presence of a 17 bp direct repeat upstream of the capsule transport region.…”
Section: Plos Pathogensmentioning
confidence: 80%
“…The N. meningitidis strains can produce polysaccharide capsules and exopolysaccharides (Table 2) with immunogenic properties and as a tool associated with pathogenicity, virulence, and typing of the bacterial strains, while N. gonorrhoea strains cannot produce immunogenic polysaccharide capsules. However, the capsule production studies suggested that N. gonorrhoea strains may express unusual capsule layer, such as polyphosphate, which may be involved in N. gonorrhoea infection but their prevention has not been demonstrated yet (56).…”
Section: Capsular Polysaccharides and Serotypingmentioning
confidence: 99%